2023
DOI: 10.2174/1573397119666230327115316
|View full text |Cite
|
Sign up to set email alerts
|

Central Sensitization in Spondyloarthritis: The Crossroads between Disease Activity, Health-related Quality of Life and Fibromyalgia

Abstract: Objective: To assess central sensitization in young patients with spondyloarthritis (SpA) and to study the associated factors with higher central sensitization scores. Methods: This was a cross-sectional study including patients with SpA (ASAS criteria) aged less than 50 years. For all patients, we collected the sociodemographic and disease characteristics data. Central sensitization was assessed using a validated tool: The Central Sensitization inventory (CSI). Pain status, fibromyalgia, quality of life, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…These results suggest that the limited sensitivity and, to a lesser extent, specificity of FiRST are probably due to differences in the perception of FM-related symptoms in patients with axSpA compared to other patients with chronic widespread pain. What seems disturbing is the widespread use of FiRST for diagnosing FM in axSpA patients in scientific research [19][20][21][22][23][24]. In studies with large patient groups, it may be tempting to use a short and simple PROM rather than a full clinical assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the limited sensitivity and, to a lesser extent, specificity of FiRST are probably due to differences in the perception of FM-related symptoms in patients with axSpA compared to other patients with chronic widespread pain. What seems disturbing is the widespread use of FiRST for diagnosing FM in axSpA patients in scientific research [19][20][21][22][23][24]. In studies with large patient groups, it may be tempting to use a short and simple PROM rather than a full clinical assessment.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no Polish language version of FiRST. Moreover, although FiRST is often used in studies with axSpA patients to determine the prevalence of FM [19][20][21][22][23][24], it has never really been validated in this group of patients. We found only one study with axSpA patients that have used FIRST and 1990 ACR classification criteria at the same time, and which have shown rather poor agreement between the screening test and the classification criteria (with κ coefficient = 0.35) [5].…”
Section: Introductionmentioning
confidence: 99%
“…This sensitivity may be due to alterations in the way that pain signals are processed in the central nervous system. Studies have shown that individuals with fibromyalgia have changes in the way that their brains respond to pain stimuli [ 2 , 3 , 99 , 102 , 103 , 104 , 105 ], which may contribute to the heightened pain sensitivity and chronic pain experienced by these individuals.…”
Section: Discussionmentioning
confidence: 99%